Youth Educators - Herbert, Susan (Daily Express, 2005)
This article presents an example of secondary school students in Trinidad and Tobago acting as critical educators on issues that are important to them, at a time when many students believe that school content seems to focus on matters that are not significant to them--the Secondary School Film Festival, in which students wrote, directed, and produced short films, which addressed very complex issues, such as migration, substance abuse, domestic violence, bullying and gangs, murder, and suicide
Keywords: Secondary school students; Student developed materials; Films; Student motivation; Trinidad and Tobago